K-13 تحسين تعلم اللغة العربية: تقييم كتاب "تعليم اللغة العربية" للصف العاشر في سياق : Optimalisasi Pembelajaran Bahasa Arab: Evaluasi Buku Ajar "Ta'limul Lugotil Arobiyyah" Kelas X Konteks K-13 - Fitriani, Namiyah; Muhaiban (Akademika : Jurnal Keagamaan dan Pendidikan, 2024)
This research article evaluates the Arabic textbook "Ta'limul Lugotil Arobiyyah" for Class X in the context of the 2013 Curriculum. This research highlights the importance of Arabic as a global language, particularly in Islamic education, and emphasizes the need for effective teaching materials to improve student learning outcomes. The analysis focuses on the textbook's alignment with the curriculum standards, the appropriateness of its content and exercises, and the overall involvement of students in the learning process. The findings show that the textbooks meet several quality criteria and are relevant to student development, although improvements are still needed in areas such as visual presentation, image alignment with content, and consistency of competency indicators. The research method used is descriptive, aiming to describe phenomena with description and validation. This research is relevant, scientific, and specific to factual data. Data collection techniques through literature studies include searching, classification, processing, and interpretation of data, allowing effective information analysis to support research. The research aims to provide insights for future improvements in Arabic teaching materials, ensuring they effectively support educational goals and foster student motivation.